2002
DOI: 10.1088/0029-5515/42/6/313
|View full text |Cite
|
Sign up to set email alerts
|

The divertor plasma characteristics in the Large Helical Device

Abstract: Divertor plasma characteristics in the Large Helical Device (LHD) have been investigated mainly by using Langmuir probes. The three-dimensional structure of the helical divertor, which is naturally produced in the heliotron-type magnetic configuration, is clearly seen in the measured particle and power deposition profiles on the divertor plates. These observations are consistent with the numerical results of field line tracing. The particle flux to the divertor plates increases almost linearly with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
131
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 28 publications
9
131
0
Order By: Relevance
“…The increase in the atom flux at the inboard-side Xpoints implies a high particle recycling in the inboard-side divertor region. The Langmuir probe measurement shows high ion fluxes onto the inboard-side divertor plates [7]. This result tends to be consistent with the present results.…”
Section: T E and N E Evaluation And Inward Neutral Fluxsupporting
confidence: 93%
“…The increase in the atom flux at the inboard-side Xpoints implies a high particle recycling in the inboard-side divertor region. The Langmuir probe measurement shows high ion fluxes onto the inboard-side divertor plates [7]. This result tends to be consistent with the present results.…”
Section: T E and N E Evaluation And Inward Neutral Fluxsupporting
confidence: 93%
“…During the operation, the magnetic axis radius went and returned 18.5 times between 3.67 m and 3.7 m. In the heliotron configuration, the heat flux density along the divertor traces changes greatly for small changes of the axis radius near 3.65-3.7 m [8,9]. The temperatures of two different divertor plates are also shown.…”
mentioning
confidence: 94%
“…The field lines in the ergodic layer are connected to the divertor plates through the edge surface layer. The connection length of the open field lines in the ergodic layer are over several hundreds meters while the field line length from the X-point to the divertor plates is a few meters for the strong poloidal component of magnetic field in the divertor region [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that particle flux position and deposition profile are mainly determined by the field lines structure on the plates [3]. However the detailed analysis of the particle flux profiles on the divertor plates has not been conducted.…”
Section: Introductionmentioning
confidence: 99%